NEUROFUZZY CONTROL STRUCTURE FOR A ROBOT MANIPULATOR - Abdalla, Dr. Turki Y.; Abduihmeed, Ammar A. (Iraqi Journal for Electrical and Electronic Engineering, 2006)
In this paper a neurofuzzy control structure is presented and used for controlling the two-link robot manipulator. A neurofuzzy networks are constructed for both the controller and for identification model of robot manipulator. The performance of the proposed structure is studied by simulation. Different operating conditions are considered. Results of simulation show good performance for the proposed control structure.